UNDERSTANDING THE GOTRANSIT E-PAYMENT SYSTEM IN GREATER JAKARTA’S PUBLIC TRANSPORTATION: INSIGHTS FROM IDT AND UTAUT - Rizkyntania, Garin; Baridwan, Zaki; Rahmanti, Virginia (JRAK, 2025)
The low adoption rate of GoTransit as a new e-payment method for KRL tickets highlights the need to understand the factors influencing users’ intention to use the system. This study aims at examining these factors by integrating the IDT and UTAUT models. An online survey was conducted with 188 respondents of GoTransit Jabodetabek users, selected using a purposive sampling method. The results showed that relative advantage, complexity, and perceived security significantly influenced the intention to use, while facilitating conditions did not. Gender was found to moderate the effect of relative advantage, but not complexity, facilitating conditions, or perceived security. Age moderated the effect of complexity, but not relative advantage, facilitating conditions, or perceived security. These findings imply that efforts to promote GoTransit adoption should focus on enhancing perceived benefits, simplifying usage, and improving security assurance, especially among different age and gender groups.